Frequency of pregnancy complications among women diagnosed with COVID-19 during pregnancy, treated at Hospital General Regional con Medicina Familiar N.° 1 in Cuernavaca, Morelos, between March 2020 and March 2022 - Rojas Campos, Efraín (2025)
Objective: To identify the most frequent pregnancy complications among women diagnosed withCOVID-19 during pregnancy between March 2020 and March 2022. Materials and methods: This descriptive, cross-sectional study was based on a review of 100 medical records of pregnant women diagnosed with COVID-19 who received care between March 2020 and March 2022. A structured questionnaire was used to collect data on variables of interest, including sociodemographic characteristics, clinical information, obstetric and gynecologic history, and pregnancy complications.A univariate analysis was conducted using measures of central tendency, frequencies and percentages, with the support of Stata 13. Results: Among the sample, 47 % were in the 31–40 age group, 86 % had a partner, 57 % were salaried employees and73 % had basic education. While 54 % of the women experienced no complications, 46 % developed complications, including moderate preterm delivery (15 %) and premature rupture of membranes (6 %). An elective cesarean section recommended by anobstetrician was the delivery method for 39 % of the women. In terms of pregnancy history, 25 % had previously given birth, 11 % had experienced a miscarriage, 25 % had undergone a cesarean section and 1 % had a history of ectopic pregnancy. Conclusions: This study is clinically relevant due to the limited data available on this topic in our country and the broader global impact of maternal mortality. Notably, nearly 50 % of the patients had a body mass index (BMI) consisting with overweight—an established risk factor for complications. Regarding gestational age at diagnosis, 67 % were in their third trimester. Mild symptoms were the most frequently reported (73 %), and type 2 diabetes mellitus was one of the associated comorbidities observed. One patient (1 %) died from severe COVID-19. This impacts national development by causing negative outcomes such as increased child morbidity and mortality, school dropouts and family breakdown.